Scabies- Major Childhood Skin Infestation in Bangladesh - An Updated Review - Rahman, Kaniz; Karim, Syed Afzalul; Khan, M Azraf H; Hasan, Sadah; Delwer, Umama Binte; Rizwana, Kashfi; Keya, Nila Akter; Rahman, Farhana; Tasnim, Nosheen; Kabir, ARM Luthful; Anwar, Kazi Selim (The Journal of Ad-din Women's Medical College, 2023)
Background: Globally distributed scabies- a highly prevalent contagious skin disease particularly infests children and elderly population. Since scabies often remain un-recognized/un-diagnosed or under-reported, but >130 million people suffer from scabies, WHO listed it under neglected tropical disease (NTD). Objective(s): This updated review focus on scabies etiology and association with socio-economic profile, water sanitation, personal hygiene, poor living condition, and environmental pollution. However, few plausible risk factors of childhood scabies have also been covered in this review. Methodology: A through computer-based literature search was performed for the period of ~two decades (2000 through 2022) utilizing four familiar search engines: Google Scholar, PubMed, Scopus and Elsevier. The search topics covered: „childhood/adult scabies‟, „etiology‟, „risk factors‟, „monthly income‟, „water sanitation „personal hygiene‟, „living conditions‟ and few others (optional). Findings: Of total 28 published articles reviewed conducted in major lower/mid income countries (LMICs) including some rich and Western ones. Overall findings revealed <12 years-old children were infested more, which was reported in more higher portions from Bangladesh alike other Afro-Asian countries. Scabies is attributed to overcrowded lower socioeconomic community, lack in knowledge/practice of poor personal hygiene, polluted environment/water-sanitation. Clinically, it is associated with intense generalized pruritus causing rash, itching/scratching, particularly during winter season. One of our community-based studies in residential Madrasahs in and around Dhak city/outskirts yielded that sharing habits of daily personal belongings (personal clothing, bed linen /towels, pajamas/lungis, etc.) were main sources of scabies transmission/scabies mite: Sarcoptes Scabiei. Alike our observations, treatment of scabies included Lot. Benzyl benzoate, Monosulfirum cream/soap, Permethrin cream, and, Lot. Ivermectin/cream for severe cases as best effective drugs to eradicate scabies mites which most of the literature agreed to irradicate scabies in ~90% children. Conclusion: Scabies, more in children and elderly people, remains associated with overcrowding, bizarre living, moist/stuffy environment, poor personal hygiene, sharing personal cloths/towels, including other factors like parental sociodemographic status and poorer household income. Public Health policy makers should address immediate intervention to mitigate these factors to ensure effective prevention and control of scabies, both among the children and elderly people. The Journal of Ad-din Women's Medical College; Vol. 10 (1), Jan 2022; p 48-62